Cytosolic phosphofructokinases are important for sugar homeostasis in leaves of Arabidopsis thaliana. (22nd September 2021) - Perby, Laura Kathrine; Richter, Simon; Weber, Konrad; Hieber, Alina Johanna; Hess, Natalia; Crocoll, Christoph; Mogensen, Helle Kildal; Pribil, Mathias; Burow, Meike; Nielsen, Tom Hamborg; Mustroph, Angelika
Abstract: Background and Aims: ATP-dependent phosphofructokinases (PFKs) catalyse phosphorylation of the carbon-1 position of fructose-6-phosphate, to form fructose-1, 6-bisphosphate. In the cytosol, this is considered a key step in channelling carbon into glycolysis. Arabidopsis thaliana has seven genes encoding PFK isoforms, two chloroplastic and five cytosolic. This study focuses on the four major cytosolic isoforms of PFK in vegetative tissues of A. thaliana . Methods: We isolated homozygous knockout individual mutants ( pfk1, pfk3, pfk6 and pfk7 ) and two double mutants ( pfk1/7 and pfk3/6 ), and characterized their growth and metabolic phenotypes. Key Results: In contrast to single mutants and the double mutant pfk3/6 for the hypoxia-responsive isoforms, the double mutant pfk1/7 had reduced PFK activity and showed a clear visual and metabolic phenotype with reduced shoot growth, early flowering and elevated hexose levels. This mutant also has an altered ratio of short/long aliphatic glucosinolates and an altered root–shoot distribution. Surprisingly, this mutant does not show any major changes in short-term carbon flux and in levels of hexose-phosphates. Conclusions: We conclude that the two isoforms PFK1 and PFK7 are important for sugar homeostasis in leaf metabolism and apparently in source–sink relationships in A. thaliana, while PFK3 and PFK6 only play a minor role under normal growth conditions.